Demand Shifting Bidding in a Hybrid System with Volatile Wind Power Generation - D.K. Agrawal D.K. Agrawal; N.P. Patidar N.P. Patidar; R.K. Nema R.K. Nema (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2012)
Price responsive demand shifting bidding mechanism is discussed as an alternative solution to deal with intermittency in wind generation. This paper proposes a formulation of social welfare equation with price responsive demand shifting bidding and economic emission dispatch with emphasis on integration of wind power. The analysis is based on the IEEE 30 bus test system generation data, with conventional and wind generation plant over a period of 24 hours. It has been demonstrated that the proposed approach leads to reduction in emission as well deal with intermittency in wind generation.